Case report: CD38-directed CAR-T cell therapy: A novel immunotherapy targeting CD38- positive blasts overcomes TKI and chemotherapy resistance of myeloid chronic myeloid leukemia in blastic phase - Cui, Qingya; Liang, Peiqi; Dai, Haiping; Cui, Wei; Cai, Mengjie; Ding, Zixuan; Ma, Qinfen; Yin, Jia; Li, Zheng; Liu, Sining; Kang, Liqing; Yao, Li; et al. (Frontiers in Immunology, 2022)
Resistance to tyrosine kinase inhibitor (TKI) is a tough problem in the treatment of chronic myeloid leukemia in blastic phase (CML-BP), which was often associated with acquired mutations in the kinase domain and not eliminating the leukemic stem cells. The efficacy of TKI or combination with chemotherapy in CML-BP remains unsatisfactory. Chimeric antigen receptor T (CAR-T) cell immunotherapy may overcome TKI and chemotherapy resistance. However, lack of ideal targetable antigens is a major obstacle for treating patients with myeloid malignancies. CD38 is known to be expressed on most (acute myeloid leukemia) AML cells, and its lack of expression on hematopoietic stem cells renders it as a potential therapeutic target for myeloid CML-BP. We develop a CD38-directed CAR-T cell therapy for AML, and two patients with myeloid CML-BP were enrolled (NCT04351022). Two patients, harboring E255K and T315I mutation in the ABL kinase domain, respectively, were resistant to multiple TKIs (imatinib, dasatinib, nilotinib, and ponatinib) and intensive chemotherapy. The blasts in the bone marrow of two patients exhibited high expression of CD38. After tumor reduction chemotherapy and lymphodepletion chemotherapy, 1 × 107 CAR-T-38 cells per kilogram of body weight were administered. They achieved minimal residual disease–negative and BCR::ABL1-negative complete remission and experienced grade II cytokine release syndrome manifesting as fever. Our data highlighted that CAR-T-38 cell therapy may overcome TKI and chemotherapy resistance in patients with myeloid CML-BP.